Phylogenetic Relationships in the Festuca-Lolium Complex (Loliinae; Poaceae): New Insights from Chloroplast Sequences - Cheng, Yajuan; Zhou, Kai; Humphreys, Mike W.; Harper, John A.; Ma, Xiao; Zhang, Xinquan; Yan, Haidong; Huang, Linkai (Frontiers in Ecology and Evolution, 2016)
The species within the Lolium/Festuca grass complex have dispersed and colonized large areas of temperate global grasslands both naturally and by human intervention. The species within this grass complex represent some of the most important grass species both for amenity and agricultural use worldwide. There has been renewed interest by grass breeders in producing hybrid combinations between these species and several countries now market Festulolium varieties as a combination of genes from both genera. The two genera have been differentiated by their inflorescence structure, but controversy has surrounded the taxonomic classification of the Lolium-Festuca complex species for several decades. In order to better understand the complexities within the Lolium/Festuca complex and their genetic background, the phylogeny of important examplers from the Lolium-Festuca complex were reconstructed. In total 40 taxa representing the Festuca and Lolium species with Vulpia myuros and Brachypodium distachyon as outgroups were sampled, using two noncoding intergenic spacers (trnQ-rps16, trnH-psbA) and one coding gene (rbcL). Maximum parsimony (MP), Bayesian inference (BI) analyses based on each partition and combined plastid DNA dataset, and median-jointing network analysis were employed. The outcomes strongly suggested that the subgen. Schedonorus has a close relationship to Lolium, and it is also proposed to move the sect. Leucopoa from subgen. Leucopoa to Subgen. Schedonorus and to separate sect. Breviaristatae from the subgen. Leucopoa. We found that F. californica could be a lineage of hybrid origin because of its intermediate placement between the “broad-leaved” and “fine-leaved” clade.